USING MULTIFUNCTIONAL FOLKLORE CARD TO ENHANCE NARRATIVE READING ACHIEVEMENT OF THE TENTH GRADERS - BELLA, RISKA; INDERAWATI, RITA; VIANTY, MACHDALENA
The objectives of this study were (1) to find out whether or not there was a significantdifference in studentsâ€™ narrative reading achievement before and after they were taught byusing multifunctional folklore card and Paragraph Shrinking strategy and (2) to find outwhether or not there was a significant difference in studentsâ€™ narrative readingachievement between those who were taught by using multifunctional folklore card andParagraph Shrinking strategy and those who were not. This study was conducted by usingquasi experimental and non-equivalent control group design was applied. The populationwere the tenth graders of MAN Sakatiga Indralaya and the sample of this study was 82students of two classes, which were divided into control group and experimental group.The data were collected using a set of reading test which consist of 30 multiple choicequestions for pretest and posttest. The data obtained were analyzed by using t-test: pairedsample t-test and independent sample t-test. The result of paired sample t-test showed themean score of pretest in experimental group was 53.70 and the mean score of posttest was74.70 (mean diff=21.00 and Ï.value=.000), it means that there was a significant differentin narrative reading achievement before and after they were taught by usingmultifunctional folklore card and paragraph shrinking strategy. Furthermore, based on theresult of independent sample t-test, it revealed that the result of posttest control was 49.34and experimental group was 74.70 (mean diff=25.36, and Ï .value=.000), so there was asignificant difference in reading achievement between the students who were taught byusing MFC and paragraph shrinking strategy and those who were not. In conclusion, therewas an enhancement of studentsâ€™ narrative reading achievement by using multifunctionalfolklore card and paragraph shrinking strategy.